Urgensi asesment psikologi pada praktik Bimbingan dan konseling dalam memberikan Layanan - Desynta Nurmilasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the context of education, assessment is a basic guideline in understanding the condition of each individual. Individuals are a very diverse part, it requires the role of counselors in understanding, identifying the problems faced. The results of this assessment can be used by counselors, psychologists and counselors. Guidance and counseling teachers play a role in assessing and analyzing the behavioral actions of the individual. So the purpose of this study provides an overview related to the purpose of the assessment as additional data collection so that it can provide accurate information when undergoing counseling services. This article uses a literature study method with a qualitative approach that comes from valid data sources. So it is hoped that it can provide an understanding of the assessment test in the field of education, especially when organizing the counseling process. Therefore, this assessment test is an important part in compiling the services that will be provided by students.